Internalisasi Pembentukan Karakter dalam Proses Pembelajaran pada SMP Negeri 37 Bulukumba - Mukri Pahmi; Muh. Ilyas Ismail; Muzakkir Muzakkir (El-Idare, 2019)
This article discusses the internalization of character formation in the learning process at SMP Negeri 37 Bulukumba. The approach used is qualitative which is reviewed based on a phenomenological. The informant in this article is the head of Madrasah and teacher of Islamic religious education. The data collection techniques used are observations and interviews. Processing techniques and data analysis through data reduction, data presentation, and verification or withdrawal of conclusions. This article shows that the implementation of character education in students at SMP Negeri 37 Bulukumba is implemented by prioritizing the creation of 8 characters, namely responsible, love of homeland, social care, tolerance, discipline, Independent, democratic, and avid reading. The character education implementation is integrated with all subjects, especially the subjects of Islamic religious education conducted in the form of intrurricular and extracurricular, both in learning and beyond learning. The strategies pursued by teachers of Islamic education in the establishment of students' character at SMP Negeri 37 Bulukumba is done through the development of students and the improvement of the religious knowledge of students.